Keberlanjutan Pembangunan Wilayah Pesisir di Kabupaten Trenggalek - Lubis, Lunariana; Wahyudi, Agus (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
The coastal area is an area that has the potential to be developed, but the coastal area must also be conserved by making efficient use of coastal resources and utilizing the function of the area in a planned and rational manner, including at Prigi Beach in Watulimo District, Trenggalek Regency. The strategy for developing coastal areas in Trenggalek Regency has been stated in Regional Regulation Number 15 of 2012 concerning Spatial Planning of Trenggalek Regency for 2012-2032. This study uses a qualitative method with a case study approach in an effort to understand the sustainability of coastal development in Trenggalek Regency. Data were obtained through observation, documentation, and interviews with the head of Bappeda (Regional Development Planning Agency of Trenggalek Regency) and the community around Prigi Beach, Trenggalek Regency. Data analysis techniques with interactive models are data collection, data condensation, data presentation and conclusion drawing. Aspects of sustainable development in Watulimo District, Trenggalek Regency include (1) ecology, the existence of Prigi Bay provides benefits in the fields of Tourism, Fisheries and Marine, namely Prigi Beach, Damas Beach, Cengkrong Beach, Mangrove Tourism Forest, Karanggongso White Sand Beach and Pearl Beach. (2) the economy, the low income of fishermen in Prigi is also influenced by natural conditions, so that the fishing process cannot take place throughout the year and (3) social, the fishermen community empowerment program in Prigi has been implemented by the Government to improve the fishing community but the program has not running optimally.